Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider the function $x^a e^{-x} y^b e^{-y}$, over the triangle defined by $x \ge 0, y \ge 0, x + y = 1$.

How can one find the maximum of such a function in terms of $a,b \ge 0$? This deeply confuses me, since the triangle is not smooth...

share|cite|improve this question
In general, if the function is continuous (as here), you find the global maximum (without restriction to your area); if inside, you are done. If not, check on the boundaries. – vonbrand Feb 26 '13 at 15:28
I don't quite understand your point. If the global maximum doesn't occur inside, then check all the outside values? – Wouter Zeldenthuis Feb 26 '13 at 15:33
On the boundaries, i.e., at the lines delimiting the triangle in this case. – vonbrand Feb 26 '13 at 15:38
up vote 2 down vote accepted



$$\begin{align*}H'_x&=y^be^{-y}x^{a-1}e^{-x}\left(a-x\right)+\lambda=0\Longrightarrow \lambda=-y^be^{-y}x^{a-1}e^{-x}\left(a-x\right)\\H'_y&=x^ae^{-x}y^{b-1}e^{-y}\left(b-y\right)+\lambda=0\Longrightarrow \lambda=-x^ae^{-x}y^{b-1}e^{-y}\left(b-y\right)\\H'_\lambda&=x+y-1=0\end{align*}$$

Compairng $\,H'_x\,,\,H'_y\,$ we get

$$x^ae^{-x}y^{b-1}e^{-y}\left(b-y\right)=y^be^{-y}x^{a-1}e^{-x}\left(a-x\right)\Longleftrightarrow x(b-y)=y(a-x)$$

but $\,H'_\lambda\,$ tells us that $\,y=1-x\,$ , so

$$x(b+x-1)=(1-x)(a-x)\Longleftrightarrow x(b-1)=a-(a+1)x\ldots$$

Try to take it from here, and remember: $\,x,y\ge 0\,$

share|cite|improve this answer

Why do you bother about smoothness of domain set limits? The main focus is the function itself.

If you don't want to use Lagrange multiplier method you can use variational calculus directly:

$$max_{x,y}F(x,y)\quad s.t.\ G(x,y)=c$$

Starting with constraint $G(x,y)=c$ must hold all the time. This will be the first equation.

Using implicit function theorem we can derive that $y=y(x)$. By strenghening the constraint and using $y=y(x)$

$$dG(x,y)=\frac{\partial G}{\partial x}dx+\frac{\partial G}{\partial y}\frac{dy}{dx}dx=0$$

$$\Rightarrow\ \frac{dy}{dx}=-\frac{\frac{\partial G}{\partial x}}{\frac{\partial G}{\partial y}} $$

Using implicit function theorem again and equating total derivative of $F(x,y)$ to zero

$$dF(x,y)=\frac{\partial F}{\partial x}dx+\frac{\partial F}{\partial y}*\frac{dy}{dx}dx=0$$

and substitiuting $\frac{dy}{dx}$

$$dF(x,y)=\bigg(\frac{\partial F}{\partial x}-\frac{\partial F}{\partial y}*\frac{\frac{\partial G}{\partial x}}{\frac{\partial G}{\partial y}}\bigg)dx=0$$

The system of equations to be solved are

$$[1]\qquad G(x,y)=c$$

$$[2]\qquad \frac{\partial F}{\partial x}-\frac{\partial F}{\partial y}*\frac{\frac{\partial G}{\partial x}}{\frac{\partial G}{\partial y}}=0$$

$\mathbb PS1:$ You would come up with the same system if you would have used LM method and eliminated $\lambda$

$\mathbb PS2:$ For your specific question $x=\frac{a}{a+b}\ y=\frac{b}{a+b}$ which are valid since $a,b>0\Rightarrow\ x,y>0$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.